Registered clinical trials targeting type 2 diabetes remission with pharmacological interventions - Nicholas Shoung; Claire Carette; Nathalie Rassy; Aurélie Phan; Jerry R. Greenfield; Frank B. Hu; Claire Rives-Lange; Sébastien Czernichow (Scientific Reports)
Abstract Systematic reviews and meta-analyses indicate that dietary interventions and metabolic surgery lead to higher rates of type 2 diabetes (T2D) remission, improving beta-cell function and insulin sensitivity. There is limited data on the effectiveness of pharmacological interventions targeting T2D remission. We aimed to search clinical trial registries and perform a systematic mapping of registered randomized clinical trials of pharmacological interventions targeting T2D remission; summarizing the existing research space, and identifying gaps for future research. We searched three clinical trial registries: Clinicaltrials.gov, the World Health Organization International Clinical Trials Registry Platform and the European Union Clinical Trials Information System on the 19th March 2024. Key outcomes included sample size, interventions, comparators, definition of T2D remission, follow-up duration, funding source, eligibility criteria, trial completion status, publication status, and availability of published results. The search yielded 1108 results, of which 34 trials were included. The majority were non-industry funded (70.6%, n = 24) and 88.2% (n = 30) of trials targeted remission of T2D diagnosed within 6 years. Approximately 56% (n = 19) of trials used pharmacological combination therapy with mainly metformin, insulin, and a glucagon-like peptide 1 (GLP-1) agonist. The majority of studies (35.3%, n = 12) did not register defined specific criteria to determine remission and there was a lack of consistency in methods of beta-cell function measurement. We suggest that future research use a standardized definition of T2D remission and the beta-cell function method. Future trials should focus on using GLP-1 receptor agonists and GIP analogs, and their role in weight loss and T2D. Registration: PROSPERO CRD42024511198